Population structure of Escherichia coli O26 : H11 with recent and repeated stx2 acquisition in multiple lineages. Issue 11 (21st November 2017) - Ogura, Yoshitoshi; Gotoh, Yasuhiro; Itoh, Takehiko; Sato, Mitsuhiko P.; Seto, Kazuko; Yoshino, Shyuji; Isobe, Junko; Etoh, Yoshiki; Kurogi, Mariko; Kimata, Keiko; Maeda, Eriko; Piérard, Denis; et al.
Abstract : A key virulence factor of enterohaemorrhagic Escherichia coli (EHEC) is the bacteriophage-encoded Shiga toxin (Stx). Stxs are classified into two types, Stx1 and Stx2, and Stx2-producing strains are thought to cause more severe infections than strains producing only Stx1. Although O26 : H11 is the second most prevalent EHEC following O157 : H7, the majority of O26 : H11 strains produce Stx1 alone. However, Stx2-producing O26 strains have increasingly been detected worldwide. Through a large-scale genome analysis, we present a global phylogenetic overview and evolutionary timescale for E. coli O26 : H11. The origin of O26 has been estimated to be 415 years ago. Sequence type 21C1 (ST21C1), one of the two sublineages of ST21, the most predominant O26 : H11 lineage worldwide, emerged 213 years ago from one of the three ST29 sublineages (ST29C2). The other ST21 lineage (ST21C2) emerged 95 years ago from ST21C1. Increases in population size occurred in the late 20th century for all of the O26 lineages, but most remarkably for ST21C2. Analysis of the distribution of stx2 -positive strains revealed the recent and repeated acquisition of the stx2 gene in multiple lineages of O26, both in ST21 and ST29. Other major EHEC virulence genes, such as type III secretion system effector genes and plasmid-encoded virulence genes, were well conserved in ST21 compared to ST29. In addition, more antimicrobial-resistance genes have accumulated in the ST21C1 lineage. Although current attention is focused on several highly virulent ST29 clones that have acquired the stx2 gene, there is also a considerable risk that the ST21 lineage could yield highly virulent clones.